Cost-effectiveness and public health impact of alternative influenza vaccination strategies in high-risk adults. Issue 42 (9th October 2017) - Raviotta, Jonathan M.; Smith, Kenneth J.; DePasse, Jay; Brown, Shawn T.; Shim, Eunha; Nowalk, Mary Patricia; Wateska, Angela; France, Glenson S.; Zimmerman, Richard K.
Highlights: Use of HD-IIV3 or RIV may increase vaccine effectiveness in high-risk adults. Use of HD-IIV3 and RIV for middle-aged, high-risk patients may increase public health benefits. Clinical trials of these vaccines in the adult, high-risk population may be warranted. Abstract: Purpose: High-dose trivalent inactivated influenza vaccine (HD-IIV3) or recombinant trivalent influenza vaccine (RIV) may increase influenza vaccine effectiveness (VE) in adults with conditions that place them at high risk for influenza complications. This analysis models the public health impact and cost-effectiveness (CE) of these vaccines for 50–64 year-olds. Methods: Markov model CE analysis compared 5 strategies in 50–64 year-olds: no vaccination; only standard-dose IIV3 offered (SD-IIV3 only), only quadrivalent influenza vaccine offered (SD-IIV4 only); high-risk patients receiving HD-IIV3, others receiving SD-IIV3 (HD-IIV3 & SD-IIV3); and high-risk patients receiving HD-IIV3, others receiving SD-IIV4 (HD-IIV3 & SD-IIV4). In a secondary analysis, RIV replaced HD-IIV3. Parameters were obtained from U.S. databases, the medical literature and extrapolations from VE estimates. Effectiveness was measured as 3%/year discounted quality adjusted life year (QALY) losses avoided. Results: The least expensive strategy was SD-IIV3 only, with total costs of 99.84/person. The SD-IIV4 only strategy cost an additional 0.91/person, or 37, 700/QALY gained. The HD-IIV3 & SD-IIV4 strategy cost 1.06 more than SD-IIV4 only, or 71, 500/QALY gained. No vaccination and HD-IIV3 & SD-IIV3 strategies were dominated. Results were sensitive to influenza incidence, vaccine cost, standard-dose VE in the entire population and high-dose VE in high-risk patients. The CE of RIV for high-risk patients was dependent on as yet unknown parameter values. Conclusions: Based on available data, using high-dose influenza vaccine or RIV in middle-aged, high-risk patients may be an economically favorable vaccination strategy with public health benefits. Clinical trials of these vaccines in this population may be warranted.